Flexible testing platform for employment of RFID-enabled multi-agent system on flexible assembly line. (January 2016) - Barenji, Ali Vatankhah; Barenji, Reza Vatankhah; Hashemipour, Majid
Highlights: The objective of this study is to examine the potential enhancement of flexible assembly line performance through the use of a radio-frequency-identification-enabled multi-agent scheduling and control system (RFID-enabled MASCS). A novel simulation test platform is developed for the examination of an RFID-enabled MASCS in a flexible assembly line, and several system performance measures are considered in the simulation test platform. The developed simulation test platform is based on a hybrid agent (HA) and uses an existing RFID-enabled MASCS architecture. Abstract: The success of a flexible assembly line (FAL) depends on efficacious scheduling and control architecture. However, the scheduling and control architectures currently employed in FALs lack the flexibility and reconfiguration capacity to manage disturbances when they occur. Consequently, the system performance rapidly degrades when the system operation is interrupted. The objective of this study is to examine the potential enhancement of FAL performance through the use of a radio-frequency-identification-enabled multi-agent scheduling and control system (RFID-enabled MASCS). A simulation test platform is developed for the examination of an RFID-enabled MASCS in a FAL, and several system performance measures are considered in the simulation test platform. The results indicate that the RFID-enabled MASCS can increase the uptime productivity and production rate of a FAL. A real case-study test is performed, and a 22% decrease in lead time along with significant improvements in other system performance indicators are observed, especially when a series of disturbances occur within the examined assembly machine.